Satellite-based method for computing air pollution index - Ahmad, Asmala; Hashim, Mazlan; Md. Hashim, Noorazuan; Ayof, Mohd Nizam; Budi, Agus Setyo (Universiti Teknikal Malaysia Melaka, 2006)
The recent August 2005 haze episode was not a new experience for Malaysia as this phenomenon has been occurring almost every year. History revealed that the worst haze episode took place during May-November 1997. On the 23rd September 1997, the Sarawak capital, Kuching was declared in the state of emergency as its Air pollution Index (API) reached 839. This was the highest API ever been recorded in Malaysia. This paper reports result of a study in order to compute API using satellite-based method. Seven dates of NOAA-14 AVHRR satellite recorded data were used, representing seven days during the September 1997 thick haze episode in Malaysia. Five locations of air pollution station were selected where major pollutants have been measured conventionally. Haze information was extracted from the satellite data using ‘sky-light’ model. Relationship between the satellite recorded reflectance and the corresponding pollutant measurement was determined using regression analysis. Finally, accuracy of the result was assessed using RMSE technique. The result proven that satellite-based method using space-borne remote sensing data was capable of computing API spatially and continuously.